Efficacy and Safety of First-Line Chemotherapies for Patients With Advanced Biliary Tract Carcinoma: A Systematic Review and Network Meta-Analysis - Jiang, Yanfeng; Zeng, Zhiming; Zeng, Jie; Liu, Cuizhen; Qiu, Jinfeng; Li, Ye; Tang, Jing; Mo, Ning; Du, Lihua; Ma, Jie (Frontiers in Oncology, 2021)
Background At present, chemotherapy is still the primary treatment for advanced biliary tract carcinoma, but it is challenging to balance the efficacy and side effects. Network meta-analysis (NMA) is a better way to identify the protocol, and the advantage is that it can be combined with direct and indirect evidence to judge the best treatment regimens. Therefore, we conducted NMA on the searched randomized controlled trials (RCTs). Methods NMA was conducted regarding the searched RCTs by comparing progression-free survival (PFS), overall survival (OS), objective remission rates (ORRs), and adverse events (AEs) of different chemotherapy protocols. Results We screened 24 studies that met the inclusion criteria for further analysis. Compared with other regimens, the best supportive care (BSC) or FUFA protocol has a worse OS. Folfox4, GEMOX+erlotinib, and C+GEMOX can improve patients’ PFS compared with BSC. Patients receiving GP+cediranib protocol have higher ORRs. There was reduced neutropenia grade ≥3 when adopting GP+cediranib, GS, C+GEMOX, RAM+GP, and MER+GP than when using FUFA protocol. The probability of vomiting of XELOX is lower than that of GEM+XELOX. There is a lower diarrhea incidence of XELOX than that of GEMOX+erlotinib. The results of cluster grade analysis illustrated that GEMOX+erlotinib owned a higher ORR and a higher surface under the cumulative ranking (SUCRA) of neutropenia and vomiting but also had a lower SUCRA of diarrhea and fatigue. Meanwhile, both GEMOX and C+GEMOX have a better ORR and a higher AE SUCRA. Conclusion The NMA demonstrated that chemotherapy combined with targeted therapy has better efficacy and lower incidence of AEs than chemotherapy alone.